The effect of sodium thiosulfate on immune cell metabolism during porcine hemorrhage and resuscitation - Wolfschmitt, Eva-Maria; Hogg, Melanie; Vogt, Josef Albert; Zink, Fabian; Wachter, Ulrich; Hezel, Felix; Zhang, Xiaomin; Hoffmann, Andrea; Gröger, Michael; Hartmann, Clair; Gässler, Holger; Datzmann, Thomas; et al. (Frontiers in Immunology, 2023)
Introduction: Sodium thiosulfate (Na2S2O3), a H2S releasing agent, was shown to be organ-protective in experimental hemorrhage. Systemic inflammation activates immune cells, which in turn show cell type-specific metabolic plasticity with modifications of mitochondrial respiratory activity. Since H2S can dose-dependently stimulate or inhibit mitochondrial respiration, we investigated the effect of Na2S2O3 on immune cell metabolism and function in a blinded, randomized, controlled, long-term, porcine model of hemorrhage and resuscitation. For this purpose, we developed a Bayesian sampling-based model for 13C isotope metabolic flux analysis (MFA) utilizing 1,2-13C2-labeled glucose, 13C6-labeled glucose, and 13C5-labeled glutamine tracers. Methods: After 3 h of hemorrhage, anesthetized and surgically instrumented swine underwent resuscitation up to a maximum of 68 h. At 2 h of shock, animals randomly received vehicle or Na2S2O3 (25 mg/kg/h for 2 h, thereafter 100 mg/kg/h until 24 h after shock). At three time points (prior to shock, 24 h post shock and 64 h post shock) PBMCs and granulocytes were isolated from whole blood, and cells were investigated regarding mitochondrial oxygen consumption (high resolution respirometry), reactive oxygen species production (electron spin resonance) and fluxes within the metabolic network (stable isotope-based MFA). Results: PBMCs showed significantly higher mitochondrial O2 uptake and lower O2•− production in comparison to granulocytes. We found that in response to Na2S2O3 administration, PBMCs but not granulocytes had an increased mitochondrial oxygen consumption combined with a transient reduction of the citrate synthase flux and an increase of acetyl-CoA channeled into other compartments, e.g., for lipid biogenesis. Conclusion: In a porcine model of hemorrhage and resuscitation, Na2S2O3 administration led to increased mitochondrial oxygen consumption combined with stimulation of lipid biogenesis in PBMCs. Granulocytes, on the other hand, remained unaffected. O2•− concentration in whole blood remained constant during shock and resuscitation, indicating a sufficient anti-oxidative capacity. Overall, our MFA model seems to be a promising approach for investigating immunometabolism; especially when combined with complementary methods.